Review of Harpactea ground-dwelling spiders (Araneae: Dysderidae) of Portugal - Řezáč, Milan; Cardoso, Pedro; Řezáčová, Veronika (Zootaxa, 2023)
We revise the Portuguese spiders of the genus Harpactea Bristowe, 1939 (Araneae: Dysderidae). The following seven new species are described: H. adicensis sp. nov., H. crespoi sp. nov., H. dolanskyi sp. nov., H. henriquesi sp. nov., H. korenkoi sp. nov., H. krejcii sp. nov. and H. pekari sp. nov. In three species, H. algarvensis Ferrández, 1990, H. minoccii Ferrández, 1982 and H. tavirensis Wunderlich, 2020 the females are described for the first time. The Portuguese Harpactea spiders belong to two species groups, namely the hombergi group and the corticalis group (sensu Deeleman-Reinhold 1993). The majority of the Portuguese representatives of the corticalis group probably constitute a monophyletic group endemic for the Iberian peninsula, the minoccii subgroup Ferrández, 1990. The synapomorphy of this clade is the unique position of partners during copulation: the male grasps one of the femaleʼs chelicerae between his chelicerae. The malesʼ chelicerae are morphologically adapted for this behaviour. Due to this unusual position during copulation the female genitalia are more distant from the male than in other Harpactea species. Therefore, the pedipalps are more elongated . Furthermore, the males of this subgroup possess larger basal part of male copulatory organ (the tegulum), where the ejaculate is stored before copulation. We observed that the males of this subgroup invest significantly more time into single copulation than the other representatives of the corticalis group with smaller tegulum. Therefore, enlargement of the tegulum might reflect different sperm competition strategy, in which males invest more ejaculate in each copulation. In Portugal, Harpactea spiders are frequently found under woody plants that produce slowly decomposing leaf litter, usually Quercus spp., or introduced Eucalyptus sp. These spiders require slightly humid substratum.